THE FORMATION OF MORAL-AESTHETIC COMPETENCE IN UNIVERSITY STUDENTS THROUGH TOURISM TOOLS - Botirovna, Abdullayeva Nargisa (PT. Antis International Publisher, 2024)
This review explores the formation of moral-aesthetic competence in university students through the utilization of tourism tools. By analyzing recent literature, it investigates how tourism-related activities contribute to the development of moral and aesthetic values among higher education students.